Numb cheek syndrome in breast cancer: a case report - Tan, Zhibin; Tan, Si Ying (Frontiers in Oncology, 2024)
Numb cheek syndrome, a rare corollary of numb chin syndrome, is due to infra-orbital neuropathy. It can occur in association with an underlying malignancy, which can cause neuropathy by direct malignant nerve infiltration or via a paraneoplastic mechanism. Although numb cheek syndrome has been reported in association with a variety of cancers, it has previously not been reported in association with breast cancer. We report a case of left breast cancer presenting with left numb cheek syndrome.A 65-year-old woman presented to the Neurology clinic with a 7-month history of left cheek numbness and occasional cheek tenderness. Examination revealed slightly diminished pin-prick sensation in the left cheek and a vaguely palpable left breast lump. A magnetic resonance imaging scan of the brain showed abnormal enhancement of the left maxillary nerve at the foramen rotundum, but cerebrospinal fluid analysis was normal. Mammography, ultrasound scans, and core biopsy of the left breast confirmed the diagnosis of invasive left breast carcinoma (estrogen and progesterone receptor negative, c-erb-B2 equivocal, fluorescence in-situ hybridization negative). There was no evidence of distant metastases on computed tomography and bone scintigraphy scans. The patient underwent neoadjuvant chemotherapy (4 cycles of doxorubicin and cyclophosphamide, followed by 4 cycles of paclitaxel and carboplatin), and left breast wide excision and sentinel lymph node biopsy, and a repeat magnetic resonance imaging scan performed 2 months after surgical resection showed resolution of the left maxillary nerve enhancement. The patient's left numb cheek symptoms improved over a course of 5 months after cancer resection but did not completely resolve. Our case represents the first reported left numb cheek syndrome in association with breast cancer, due to maxillary neuropathy without any discrete mass or compressive cause. To avoid delays in diagnosing malignancy, physicians and surgeons should be aware that numb cheek syndrome can occur in association with an underlying malignancy, and that breast cancer should be counted amongst the possibilities.